Intravoxel incoherent motion MRI in differentiation between recurrent carcinoma and postchemoradiation fibrosis of the skull base in patients with nasopharyngeal carcinoma. Issue 6 (26th May 2016) - Mao, Jiaji; Shen, Jun; Yang, Qihua; Yu, Taihui; Duan, Xiaohui; Zhong, Jinglian; Phuyal, Prakash; Liang, Biling
Abstract : Purpose: To determine the capacity of intravoxel incoherent motion (IVIM) magnetic resonance imaging (MRI) in differential diagnosis between recurrent carcinoma and postchemoradiation fibrosis of skull base in patients with nasopharyngeal carcinoma (NPC). Materials and Methods: Eleven patients with recurrent NPC and 21 patients with postchemoradiation fibrosis in the skull base were enrolled. All the diagnoses were proved by endoscopic biopsy or imaging follow‐up. IVIM MRI was performed to obtain quantitative parameters including D (pure diffusion), f (perfusion fraction), and D* (pseudodiffusion). D, f, and D* were compared between two groups; the diagnostic performances of D and f were evaluated using the receiver operating characteristic (ROC) analysis. Results: D and f values were significantly lower in recurrent carcinoma than that in fibrosis ( P < 0.001; P  = 0.001). No significant difference was found in D* values between recurrent carcinoma and fibrosis ( P  = 0.229). ROC curve analysis showed that the area under the curve of D and f values were 0.996 and 0.838, respectively. Respective cutoff values with sensitivity, specificity, and accuracy were: D = 1.161 × 10 −3 mm 2 /s (sensitivity 100.0%, specificity 95.2%, accuracy 96.9%), f = 0.109 (sensitivity 81.8%, specificity 71.4%, accuracy 75.0%). Conclusion: Recurrent NPC and postchemoradiation fibrosis in the skull base have distinctive D and f values. IVIM MRI could be used to differentiate between recurrent carcinoma and postchemoradiation fibrosis in patients with NPC. J. Magn. Reson. Imaging 2016;44:1556–1564.